Presence of airborne microplastics in human lung tissue - Amato-Lourenço, Luís Fernando; Carvalho-Oliveira, Regiani; Júnior, Gabriel Ribeiro; dos Santos Galvão, Luciana; Ando, Rômulo Augusto; Mauad, Thais (Journal of hazardous materials, 2021)
Plastics are ubiquitously used by societies, but most of the plastic waste is deposited in landfills and in the natural environment. Their degradation into submillimetre fragments, called microplastics, is a growing concern due to potential adverse effects on the environment and human health. Microplastics are present in the air and may be inhaled by humans, but whether they have deleterious effects on the respiratory system remain unknown. In this study, we determined the presence of microplastics in human lung tissues obtained at autopsies. Polymeric particles (n = 33) and fibres (n = 4) were observed in 13 of 20 tissue samples. All polymeric particles were smaller than 5.5 µm in size, and fibres ranged from 8.12 to 16.8 µm. The most frequently determined polymers were polyethylene and polypropylene. Deleterious health outcomes may be related to the heterogeneous characteristics of these contaminants in the respiratory system following inhalation. [Display omitted] •Microplastics may be present in human lung tissue.•For the first time microplastics in lung were characterized using Raman spectroscopy.•Particles of the most produced and consumed plastics ranged from 1.60 to 5.56 µm.•The study sheds new light on the level of human exposure to airborne microplastics.